Oral self-care behavior and its influencing factors in a sample of school children from Central Iran - Iraj Zareban; Mahmood Karimy; Marzieh Araban; Daniel Delaney (BMC, 2021)
Abstract Background Oral health is an important part of public health and crucial to health promotion and enhancing the quality of life. This research examined childhood oral self-care behavior and their related factors using extended Theory of Planned Behavior (TPB). Method This cross-sectional study was conducted on 368 sixth-grade elementary school students in Saveh city, Iran, in 2019. The students were selected using a random multi-stage sampling method. The instrument included the socio-demographic questions, TPB constructs, and action and coping plan items. Data were analyzed by SPSS software (Version 21) at alpha level p ≤ 0.05. Result Overall, 24 (6.6%) students have never used toothbrushes, 222 (62.7%) have never used dental floss, and 298 (82.7%) students have never used mouthwash. The stepwise multiple linear regression analysis results indicated that the TPB with action and coping planning constructs had better predictive power than the original model. In the final model, coping planning (β = .28), intention (β = .24), action planning (β = .23), and perceived behavior control (β = .15) were the most important predictors of oral self-care behavior. Conclusion The results indicated that the oral self-care behavior status in Iranian elementary students was not favorable, and the extended model of the TPB with action and coping plan constructs were significant predictors of self-care behavior. Therefore, these findings emphasize the need for expanding educational interventions based on the extended model of the TPB to improve the oral self-care behavior of students.